A Theological critique of the Christian pacifist perspective with special reference to the position of John Howard Yoder - Russell, David (Department of Religious Studies, 2016)
This study is an exercise in theological critique of the Christian pacifist position of John Howard Yoder, with a view to engaging in the theological debate on violence and non-violence. Given the wide ranging nature of this debate it is, however, necessary to ground such a discussion in a given context. South Africa has been chosen for this purpose because of my own sense of shared responsibility for the healing of this land in which I was born. The problem of violence, together with the use of force and power, is an area of ethics where the definition and clarification of terms is of particular importance. Words like 'violence' are used in different ways which, more often than not, reflect the perspective of the one employing them. Chapter 1 is, therefore, devoted to the attempt to clarify and define certain key concepts, and to draw attention to the inherent ambiguity attached to terms like 'violence', 'non-violence', and 'pacifism'. This thesis is not primarily concerned to analyse South African society. It is, first and foremost, a study in theological ethics concerning the use of force. Nevertheless, a brief outline of the South African situation has been presented, for two reasons. Firstly, no theology, and manifestly no theological ethics, can usefully be undertaken except in relation to the actualities of life. Secondly, the motivation for this study derives from being involved in this specific situation of violence. In Chapter 2, therefore, some description and analysis of South African society is given, simply in order to ground this study in a context. In reflecting upon the ethics of the use of force and the problem of violence, the challenge of the pacifist option is first considered. Given the wide variety of positions within the pacifist perspective, one highly regarded exponent of this tradition has been chosen, namely, John Howard Yoder. Yoder's position is presented in Chapter 3. In Chapter 4 a critical evaluation of this position is undertaken. This constitutes the central focus of this study. Apart from certain positive aspects, areas of criticism are analysed in depth. These concern the way in which Jesus is portrayed in the Gospels, and the debate around the implications of this for disciples. A further area concerns the debate around the nature and limitations of man's responsibility for wielding power as stewards of God's world. Finally, the complex issue of the reality of ambiguous moral situations is raised and analysed. The conclusion reached is that Yoder's position, though powerfully argued, is nevertheless unconvincing in certain respects. His claim that "every member of the body of Christ is called to absolute non-resistance in discipleship" is challenged, both in terms of biblical exegesis, and in terms of the nature of human responsibility to control the abuse of force in the world. On the other hand, it is conceded that Yoder's criticism of the alternative position has a certain validity. In this instance, his criticism is levelled more specifically at the methodology which Karl Barth employs in his theological ethics. This is evaluated in Chapter 5, and leads to a consideration of the methodological problem as it affects all ethics. A way through is suggested, which takes Yoder's criticisms into account while, at the same time, upholding the validity of Barth's position in its essentials, namely, that there are times when Christians can and must make ethical decisions which constitute a departure from, or exception to, the norm as commonly understood. Having analysed the methodological problem and suggested a tentative solution or way through, an alternative response is then presented and evaluated in Chapter 6. This is undertaken as an appropriate extension of the critique of Yoder's Christian pacifist position. If the latter position is found wanting, it is necessary for the sake of completion to suggest an alternative which is more viable. In this chapter, just-war theory is evaluated in some detail. The conclusion is that just-war theory remains a necessary and useful tool for the theological analysis of conflict and that, furthermore, it has a direct and important bearing on the ethical questions raised in the introduction to this study. These questions concern the debate over the involvement by Christians in the struggle for a more just and human society. Finally, in an unconcluding postscript, it is pointed out that a viable attempt to apply the theological conclusions would not be possible without a far more extended analysis of the situation itself. Such an extended analysis would require another major study. All that is possible, therefore, is to suggest some indications as to how the just-war theory might begin to be applied in this specific situation.